Review article: experimental therapies in autoimmune hepatitis. Issue 7 (14th August 2020) - Halliday, Neil; Dyson, Jessica Katharine; Thorburn, Douglas; Lohse, Ansgar W.; Heneghan, Michael A.
Summary: Background: Current therapeutic options for autoimmune hepatitis (AIH) are limited by adverse events associated with corticosteroids and thiopurines and the limited evidence base for second‐ and third‐line treatment options. Furthermore, current treatment approaches require long‐term exposure of patients to pharmacological agents. There have been significant advances in the understanding of the mechanisms underpinning autoimmunity and an expansion in the available therapeutic agents for suppressing autoimmune responses or potentially restoring self‐tolerance. Aim: To review the mechanisms and evidence for experimental therapies that are being actively explored in the management of AIH. Methods: We have reviewed the literature relating to a range of novel therapeutic immunomodulatory treatment strategies and drugs. Results: Drugs which block B cell‐activating factor of the tumour necrosis factor family (BAFF) and tumour necrosis factor α are currently in clinical trials for the treatment of AIH. Experimental therapies and technologies to increase immune tolerance, such as pre‐implantation factor and regulatory T cell therapies, are undergoing development for application in autoimmune disorders. There is also evidence for targeting inflammatory pathways to control other autoimmune conditions, such as blockade of IL1 and IL6 and Janus‐associated kinase (JAK) inhibitors. Conclusions: With the range of tools available to clinicians and patients increasing, it is likely that the therapeutic landscape of AIH will change over the coming years and treatment approaches offering lower corticosteroid use and aiming to restore immune self‐tolerance should be sought.